Pengaruh Harga, Ulasan dan Tampilan Produk terhadap Keputusan Pembelian Produk Fashion pada Marketplace Shopee di Cibeureum Kota Cimahi - Ayi Muhiban; Rizky Alamsyah (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research aims to examine the influence of price, reviews, and product display on the purchasing decisions of fashion products, with a special focus on the Shopee marketplace. The study was conducted in the Cibeureum area of Cimahi City. This research uses a quantitative approach with a survey method, distributing questionnaires specifically to Shopee marketplace users, with a total of 99 respondents to collect data. The results of this study indicate that price, reviews, and product display have a positive and significant impact on the purchasing decisions of fashion products in Cibeureum, Cimahi City. Price is generally rated well, although certain aspects such as product quality have weaknesses. Reviews are also rated well, although there are weaknesses such as the information aspect still being a drawback. Similarly, product display is rated well but there are areas that need improvement, such as differentiating Shopee’s product display from other marketplaces. This study concludes that price, reviews, and product display positively and significantly influence the purchasing decisions of fashion products on the Shopee marketplace. The implication of this research is that Shopee can review the differences in product display design on Shopee compared to other marketplaces to make it more attractive, pay attention to information regarding product prices to ensure they align with market prices, and enhance consumer satisfaction.